Integration needs and consistency evaluation for requirement analysis in CIM development - Kayaligil, S; Hashemipour, M (Inderscience Enterprises Ltd, 2001)
Computer integrated manufacturing (CIM) offers many unprecedented opportunities, but also unique challenges to undertake in getting the existing fully (or even partially) manual applications adapted. These difficulties in general multiply if the transition takes place in SME, especially on the overall company scale. Requirement analysis is the initiation task in such projects, and undoubtably the most critical in getting a useful conceptual model of what to expect at the very end. We took a staged approach to the general requirement analysis process in our earlier work in this field for the last few years and now complement these with the final stage covering integration needs analysis. The distinguishing feature of this stage is that it addresses dynamic aspects by introducing ELH diagrams and a modified form of GRAI nets and integrity issues in particular whereas the previous stages are involved with the static characteristics and logical consistency. Specific rules corresponding novel means of analysis are proposed to enable an effective examination of integrity. The outcome of our effort is a systematised set of relations and criteria, in assessing the suitability of specifications to be looked for in prospective CIM installations, based on requirements set forth at the outset.
Keywords: CIM; integration needs; consistency analysis